2021
DOI: 10.1182/blood.2020006923
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota diversity disruption and clinical outcomes after auto-HCT: a multicenter observational study

Abstract: We have previously described clinically relevant reductions in fecal microbiota diversity of patients undergoing allogeneic hematopoietic cell transplantation (allo-HCT). Recipients of high-dose chemotherapy and autologous hematopoietic cell transplantation (auto-HCT) incur similar antibiotic exposures and nutritional alterations. To characterize the fecal microbiota in the auto-HCT population, we analyzed 1,161 fecal samples collected from 534 adult recipients of auto-HCT for lymphoma, myeloma and amyloidosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 71 publications
1
46
0
Order By: Relevance
“…Similar conclusions were drawn from the results of the small pilot study with 15 patients, showing that baseline microbiota were associated with subsequent incidence and severity of nausea, vomiting, neutropenic fever, and rate of neutrophil engraftment (90). Khan et al showed recently that 534 adult recipients of highdose chemotherapy with ASCT had significantly decreased alpha diversity at early pretransplant stages than healthy individuals and that this reduction in diversity tended to be more marked in the course of the procedure (9). The pattern of this loss of diversity and dominance of specific taxa were similar to those seen in patients after alloSCT.…”
Section: Antimicrobialsmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar conclusions were drawn from the results of the small pilot study with 15 patients, showing that baseline microbiota were associated with subsequent incidence and severity of nausea, vomiting, neutropenic fever, and rate of neutrophil engraftment (90). Khan et al showed recently that 534 adult recipients of highdose chemotherapy with ASCT had significantly decreased alpha diversity at early pretransplant stages than healthy individuals and that this reduction in diversity tended to be more marked in the course of the procedure (9). The pattern of this loss of diversity and dominance of specific taxa were similar to those seen in patients after alloSCT.…”
Section: Antimicrobialsmentioning
confidence: 79%
“…Recent studies have yielded plenty of information on the differences in microbiota among MM patients and about longitudinal changes acquired during the treatment as well (9). Some recently identified gut microbes are responsible for inducing an inflammatory environment, both within the gut layer and throughout the whole body.…”
Section: Introduction -Pathogenesis Of Plasma Cell Dyscrasiasmentioning
confidence: 99%
“…A large multicenter observational study has confirmed lower mortality rates in patients showing higher diversity of intestinal microbiota at engraftment (3). Recently, microbiota injury has been observed also in recipients of autologous HSCT, who undergo similar antibiotic exposures and nutritional alterations after high-dose chemotherapy and transplant procedure (80). Reduced OS and PFS have been reported in patients with lower peri-engraftment microbiome diversity.…”
Section: Role Of Intestinal Microbiota In Hematopoietic Stem Cell Transplantation Correlation With Hsct Outcomesmentioning
confidence: 84%
“…Khan and colleagues highlighted interesting similarities in gut microbiota dysbiosis after both autologous- and allogeneic-HSCT in MM patients ( 89 ). Changes in the bacteriome and mycobiome also modulate early toxicity and the rate of neutrophil engraftment after autologous-HSCT ( 90 ).…”
Section: Role Of the Gut Microbiota In Hematopoietic Stem Cell Transp...mentioning
confidence: 99%